Transurgical Approach and Postoperative Follow-Up of a Canine with a Splenic-Azygos Shunt - Medeiros, Alice Morais; Nunes Júnior, Juarez Simões; Tavares Mathias, Carlos Henriques; Viera Gonçalves, Dariele dos Santos; Bortolotti de Carvalho, Luiza; de Castro Conti, Laura Monteiro; Piccoli Rangel, Júlia da Penha; de Souza Monteiro, Betânia (Acta Scientiae Veterinariae, 2020)
Background: The most frequent hepatic circulatory abnormality in dogs is the portosystemic shunt, characterized by an atypical deviation of the hepatic blood flow, that causes the blood that should be drained by the liver through the portal vein to be diverted to another systemic vein, as a result of the presence of the anomalous vessel. This diversion leads to reduced hepatic blood flow and, consequently, organ dysfunction, along with the accumulation of many toxins in the circulation, for instance, ammonia and short-chain fatty acids. The main objective of this paper is to Report the clinical case of a canine female diagnosed with an extrahepatic portosystemic shunt and submitted to surgical treatment using an ameroid constrictor ring in the obstruction of the anomalous vessel. Case: A canine Shih-Tzu, at the age of 1 year and 8 months, was brought to the Veterinary Hospital presenting a history of emesis and smaller body structure than other animals from the same litter. The animal had been diagnosed with portosystemic shunt at age 1 month, by means of complementary biochemistry, ultrasonography and computed tomography examinations. The latter identified the anomalous vessel, which originated from the left gastric vein and was inserted into the azygos vein in the portohepatic region. During the surgical intervention, after median pre-retro-umbilical celiotomy, a calibrous vessel was identified, coming out of the junction of two splenic veins and a gastric vein that penetrated the diaphragm and connected to the azygos vein in the thorax before flowing into the vena cava. Given that, the diaphragm had to be sectioned, which lead to the loss of the negative intra-thoracic pressure, requiring muscle suturing to restore it. A small dissection was performed around the vessel for the ameroid constrictor placement. There was no complication during the procedure. Ten days after the surgery, the clinical evaluation and new blood tests showed that the patient was active, did not express pain and was fully recovered. Ten days after the first follow-up visit, the owners mentioned that the patient was reluctant to eat the prescribed diet, though she was clinically well and her blood test results were within normal ranges for the species. The animal did not have any episodes of apathy, anorexia or vomiting, gained weight (4.2 kg) and the clinical evolution was confirmed by the normality of the blood tests at the subsequent postoperative return visits (60, 180 and 356 days after the surgery). A year after the intervention, imaging exams were repeated and showed normal direction and velocity of the portal flow for the entire extra- and intrahepatic portal extension, liver growth with dimensions compatible with the species, and no blood flow in the anomalous vessel, as well as the presence of a radiopaque structure in the left epigastric region. Discussion: Regarding the choice of anesthetic protocols for these patients, attention had to be paid to the choice of drugs since the liver was already compromised and most drugs are metabolized in the liver. When it comes to the surgical procedure, the most common surgical complication would be portal hypertension, which occurs when total ligation of the anomalous vessel is performed. Although the surgical treatment is extremely challenging, the obstruction of abnormal blood flow of an anomalous vessel achieved by surgical placement of an ameroid ring was able to correct the hemodynamic changes presented by the patient, and to reverse the hepatic insufficiency and the increase in the size of the liver.